Genetic spectrum and clinical presentation of congenital adrenal hyperplasia in an Egyptian cohort: Insights from Alexandria University Children's Hospital - Fawzy, Dina Abdelmoneim Fawzy diab; Thabet, Mohammed Alaa; Soliman, Ashraf Tawfeeq; Marzouk, Iman; elneely, Dalia; Elsayed, Shaymaa (Acta Biomedica Atenei Parmensis, 2024)
Background: Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders affecting adrenal steroid synthesis, with 21-hydroxylase deficiency (21-OHD) being the most common form. The genetic and clinical spectrum of CAH varies globally, necessitating region-specific studies to optimize diagnosis and treatment. Objectives: This study aimed to analyze genetic mutations, clinical presentations, and biochemical control in CAH patients at Alexandria University Children's Hospital (AUCH), Alexandria, Egypt. Methods: We enrolled 90 patients with suspected CAH based on clinical and biochemical markers. Genetic testing was conducted, excluding 14 patients with no gene mutations. Data on demographics, genetic mutations, zygosity, consanguinity, clinical presentations, biochemical profiles, and treatment compliance were collected and analyzed. Results: 76 genetically confirmed CAH patients were studied. CYP21A2 mutations were the most prevalent (71%), followed by CYP11B1 mutations (23.7%). Mutations in HSD3B2, CYP19A1, and STAR each accounted for about 1%. Consanguinity was reported in 76.3% of cases. Clinical presentations included adrenal crisis (22.4%), atypical genitalia (31.6%), and both (31.6%). Good compliance was observed in 71.1% of patients, with 67.1% achieving normal 17(OH) progesterone levels and 76.3% maintaining normal ACTH levels. Discussion: Our findings confirm CYP21A2 as the predominant mutation. However, the higher prevalence of CYP11B1 mutations suggests regional genetic particularities. The high consanguinity rate influenced mutation distribution and homozygosity. Conclusion: The study underscores the genetic diversity and clinical variability of CAH in Egypt. Effective management and comprehensive genetic analysis are crucial for improving patient outcomes. The proportion of uncharacterized cases highlights the need for advanced genetic testing